2016
DOI: 10.1097/aap.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triamcinolone Levels Following Interlaminar Epidural Injection

Abstract: The pharmacokinetics of epidural-administered triamcinolone is consistent with previously observed adverse effects of the drug on endocrine function. The pharmacokinetics of other epidural-administered steroids should be determined and incorporated in clinical trials to investigate the potential associations between serum levels, clinical outcomes, and potential adverse endocrine effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…The half‐life of triamcinolone following an intra‐articular knee injection ranged from 77 hours to 154 hours . However, in a prospective study of 10 patients with chronic lumbar spine pain, the median half‐life of triamcinolone following a single epidural injection was 523 hours . The half‐life following intra‐articular facet joint injections was between the half‐life of intra‐articular knee and lumbar epidural injections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The half‐life of triamcinolone following an intra‐articular knee injection ranged from 77 hours to 154 hours . However, in a prospective study of 10 patients with chronic lumbar spine pain, the median half‐life of triamcinolone following a single epidural injection was 523 hours . The half‐life following intra‐articular facet joint injections was between the half‐life of intra‐articular knee and lumbar epidural injections.…”
Section: Discussionmentioning
confidence: 99%
“…The half‐life following intra‐articular facet joint injections was between the half‐life of intra‐articular knee and lumbar epidural injections. The clearance of triamcinolone following an intra‐articular knee injection was determined by first‐order absorption and elimination . However, following epidural administration, clearance was determined by (1) first‐order dissolution from the drug suspension, (2) redistribution and absorption from fat within the epidural space, and (3) elimination .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We doubt if the steroid that was injected epidurally prevented the development of HR. A study on the pharmacokinetics of interlaminar epidural triamcinolone showed a median time to maximum concentration of 24.2 hours and a median peak plasma concentration of 4.1 ng/mL 20. Most HRs occur within 1 hour, with 70% of the immediate symptoms occurring within the first 5–15 min 3…”
Section: Discussionmentioning
confidence: 99%